An Eye Opener for a Blinding Disease—Orbital Infarction Syndrome - Kaushik, Kavya S.; Acharya, Ullas V.; Pandey, Paritosh; Krupa, Lakshmi (Indian Journal of Radiology and Imaging, 2024)
Orbital infarction syndrome (OIS) is a disease of rare occurrence owing to the rich orbital vascular anastomotic network. We describe a case of a middle-aged female who presented with an acute left middle cerebral artery (MCA) territory infarct with left terminal internal carotid artery and MCA occlusion, underwent emergency mechanical thrombectomy, and developed painful loss of vision shortly after diagnosed as OIS based on clinical and radiological findings. The rarity and severity of OIS, especially in the setting of mechanical thrombectomy, warrant radiologists to be aware of this entity to ensure preventive measures or aid in prompt diagnosis to institute timely treatment.
Keywords: mechanical thrombectomy; OIS; orbital infarction syndrome; stroke